Podpora firemních procesů s využitím IT - Beránek, Marek (Vysoké učení technické v Brně. Fakulta podnikatelská, 2007)
Diplomová práce se zabývá podporou firemních procesu IT v projekční kanceláři. Zavedení systému CRM umožňuje monitorovat a efektivně řídí vztahy se zákazníky. Tato podpora vede k optimalizaci firemních procesu.

Master's Thesis deals with firm's IT support used in the engineer's office. Implementation of CRM system enables to monitor and lead customer relationship in more effective way. This support leads to optimization of firm's processes.
Support of firm processes with usage of IT
Keywords: CRM; systém; zákazník; CRM; system; customer